Mechanical unloading reduces microtubule actin crosslinking factor 1 expression to inhibit β‐catenin signaling and osteoblast proliferation. Issue 7 (23rd January 2018) - Yin, Chong; Zhang, Yan; Hu, Lifang; Tian, Ye; Chen, Zhihao; Li, Dijie; Zhao, Fan; Su, Peihong; Ma, Xiaoli; Zhang, Ge; Miao, Zhiping; Wang, Liping; et al.
Abstract : Mechanical unloading was considered a major threat to bone homeostasis, and has been shown to decrease osteoblast proliferation although the underlying mechanism is unclear. Microtubule actin crosslinking factor 1 (MACF1) is a cytoskeletal protein that regulates cellular processes and Wnt/β‐catenin pathway, an essential signaling pathway for osteoblasts. However, the relationship between MACF1 expression and mechanical unloading, and the function and the associated mechanisms of MACF1 in regulating osteoblast proliferation are unclear. This study investigated effects of mechanical unloading on MACF1 expression levels in cultured MC3T3‐E1 osteoblastic cells and in femurs of mice with hind limb unloading; and it also examined the role and potential action mechanisms of MACF1 in osteoblast proliferation in MACF1‐knockdown, overexpressed or control MC3T3‐E1 cells treated with or without the mechanical unloading condition. Results showed that the mechanical unloading condition inhibited osteoblast proliferation and MACF1 expression in MC3T3‐E1 osteoblastic cells and mouse femurs. MACF1 knockdown decreased osteoblast proliferation, while MACF1 overexpression increased it. The inhibitory effect of mechanical unloading on osteoblast proliferation also changed with MACF1 expression levels. Furthermore, MACF1 was found to enhance β‐catenin expression and activity, and mechanical unloading decreased β‐catenin expression through MACF1. Moreover, β‐catenin was found an important regulator of osteoblast proliferation, as its preservation by treatment with its agonist lithium attenuated the inhibitory effects of MACF1‐knockdown or mechanical unloading on osteoblast proliferation. Taken together, mechanical unloading decreases MACF1 expression, and MACF1 up‐regulates osteoblast proliferation through enhancing β‐catenin signaling. This study has thus provided a mechanism for mechanical unloading‐induced inhibited osteoblast proliferation. Abstract : Mechanical unloading decreases MACF1 expression, and MACF1 up‐regulates osteoblast proliferation through enhancing β‐catenin signaling. This study has thus provided a mechanism for mechanical unloading‐induced inhibited osteoblast proliferation.